Mental toughness among track and field national athletes and collegiate athletes - Giron Jr., Edwin B. 1999-
The study's main objective is to determine the overall level of mental toughness of national athletes and collegiate athletes. Additionally, the mental toughness scores of national and collegiate athletes with regards to Alan Heary's (2015) test of the 4Cs (Control, Commitment, Concentration, and confidence) will be compared. The Mental Toughness score will fall into three categories: 0-4 (Thriving), 5-14 (Surviving), and 15-24 (Struggling). The study will include 108 participants, 45 national athletes (M= 29, F=16) and 63 collegiate athletes (M=31, F- 32). The study used a quantitative research design, an independent t-test was used to determine whether there is a significant difference between national athletes and collegiate athletes overall mental toughness and each component of the 4Cs model. The alpha level of significance was set to 0.05. The result of the study found that the mental toughness of national athletes is better than the collegiate athletes. Additionally, the result showed that even in all 4Cs components, the national athlete's mental toughness score is lower, which means they perform better than collegiate athletes